Clinical and Biochemical Profile of Nutritional Rickets in Infants: A Study from Peshawar - Tanveer Hussain; Tahir Saeed Siddiqui (Journal of the Dow University of Health Sciences, 2018)
Objective: To determine the factors associated with nutritional rickets among infants in Peshawar and its surrounding.